2019
DOI: 10.1111/jcmm.14340
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside ameliorates Adriamycin nephropathy in mice by inhibiting β‐catenin activity

Abstract: Salidroside is a major phenylethanoid glycoside in Rhodiola rosea L., a traditional Chinese medicine, with multiple biological activities. It has been shown that salidroside possesses protective effects for alleviating diabetic renal dysfunction, contrast‐induced‐nephropathy and other kidney diseases. However, the involved molecular mechanism was still not understood well. Herein, we examined the protective effects of salidroside in mice with Adriamycin (ADR)‐induced nephropathy and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…This also happens in the CC after CN damage (Kim et al., 2018; Rockey et al., 2015). In our study, we observed the anti‐corporal fibrosis effects of both salidroside and rapamycin on penile tissue, which is in line with the anti‐fibrosis effect on other organ tissues (Chen et al., 2019; Chung et al., 2016; Farrar et al., 2015; Huang et al., 2019).…”
Section: Discussionsupporting
confidence: 86%
“…This also happens in the CC after CN damage (Kim et al., 2018; Rockey et al., 2015). In our study, we observed the anti‐corporal fibrosis effects of both salidroside and rapamycin on penile tissue, which is in line with the anti‐fibrosis effect on other organ tissues (Chen et al., 2019; Chung et al., 2016; Farrar et al., 2015; Huang et al., 2019).…”
Section: Discussionsupporting
confidence: 86%
“…This has been also shown previously in high glucose-treated cells and diabetic kidneys of rats. 25,39 Such an unexpected increase in Akt activation could be due to the parallel observed increase in TGF-β1 (described below). Indeed, TGFβ-1 is a potent stimulator of the PI3K/Akt axis.…”
Section: F I G U R E 4 Masson's Trichrome Staining Of the Kidneys Of mentioning
confidence: 87%
“…21 Interestingly, and independent of its hypoglycaemic effect, Salidroside prevented renal damage and reduces kidney fibrosis and glomerulosclerosis in Adriamycintreated mice by suppressing β-catenin signalling. 25 Also, Salidroside protected renal tubular epithelial cells from hypoxia/ reoxygenation induced apoptosis suppression of ROS, inflammation, and intrinsic cell death. 26 However, the effect of Salidroside on β-catenin signalling pathways in diabetic kidneys is completely lacking.…”
mentioning
confidence: 95%
“…To the best of our knowledge, this is the first study to have shown that ADR stimulation enhances nephrin ubiquitination, a key component of slit diaphragm membranes ( Oh et al, 2004 ; Qin et al, 2009 ; New et al, 2014 , 2016 ). Previous reports have shown that ADR regulates nephrin protein levels through nuclear transcription ( Yu et al, 2016 ; Huang et al, 2019 ; Wang et al, 2020 ). Meyer-Schwesinger et al (2009) observed that the levels of ubiquitin-modifying enzyme ubiquitin C-terminal hydrolase-L1 in podocytes was increased in the biopsies of patients with membranous nephropathy, focal segmental glomerulosclerosis, and lupus nephritis IV.…”
Section: Discussionmentioning
confidence: 99%